Apicomplexan and non-metazoan microeukaryotes in the thermosensitive reef-building coral Acropora hyacinthus shift in abundance throughout an extreme coral bleaching event - Athena Peterson; Sunni Patton; Emily R. Schmeltzer; Carsten G. B. Grupstra; Lauren I. Howe-Kerr; J. Grace Klinges; Rebecca L. Maher; Adriana Messyasz; Sarah Seabrook; Andrew R. Thurber; Adrienne M. S. Correa; Rebecca L. Vega Thurber (Frontiers in Marine Science, 2025)
Coral reefs play vital roles in global marine systems and are currently facing increased threats of bleaching. Coral bleaching is heavily influenced by the host-associated microeukaryote community – most notably the dinoflagellate family Symbiodiniaceae. The apicomplexan family Corallicolidae, is the second most abundant member of the microeukaryote community, yet their role in coral health is largely unknown. To explore the role that this apicomplexan and the greater non-metazoan microeukaryotic community play in coral health, samples of a thermally sensitive scleractinian coral, Acropora hyacinthus , were collected over the course of a severe coral bleaching event and its aftermath. Through 18S rRNA gene sequencing analysis, we found that taxa within the family Corallicolidae were relatively enriched in corals during, and immediately after, the severe bleaching event as compared to before or one year after. Although utilizing 18S rRNA gene sequencing methods is not the standard for Symbiodiniaceae community profiling, we were able to observe symbiont shuffling among the Symbiodiniaceae communities, as the dominant algal symbiont shifted from the genus Cladocopium to the genus Symbiodinium following the bleaching event. Furthermore, the non-metazoan microeukaryote community displayed a general shift towards a state of dysbiosis; evidenced by substantial changes in both microeukaryote community composition and dispersion. These results offer insight into the dynamics of apicomplexans throughout the course of an increasingly common global coral reef stressor.

Forest restoration can bolster salmon population persistence under climate change - Michele S. Buonanduci; Eric R. Buhle; Michael J. Case; Emily R. Howe; James C. Robertson; Nicholas VanBuskirk; Ailene K. Ettinger (Biological Conservation, 2025)

Embryotoxicity of statins and other prescribed drugs with reported off-target effects on cholesterol biosynthesis - Taryn Hartley; Hagir Abdelmagid; Zeenat Abdulsalam; Aliyah Mansion; Emily Howe; Daniel Ramirez; Kaylei White; Emmanuel Tadjuidje (Reproductive Toxicology, 2025)

Relative humidity, temperature, and hypertensive disorders of pregnancy: Findings from the Project Viva cohort - Christina M. Howe; Brent A. Coull; Stefania Papatheodorou; Heike Luttmann-Gibson; Sheryl L. Rifas-Shiman; Ander Wilson; Itai Kloog; Qian Di; Antonella Zanobetti; Petros Koutrakis; Joel D. Schwartz; Emily Oken; et al. (Environmental Research, 2024)

The where, when, and how of ooid formation: What ooids tell us about ancient seawater chemistry - Bolton Howes; Akshay Mehra; Emily Geyman; Julia Wilcots; Ryan Manzuk; Curtis Deutsch; Adam Maloof (Earth and Planetary Science Letters, 2024)

Characterization of recent wild pig-vehicle collisions in Georgia, USA - Jeremiah L. Psiropoulos; Emily Howe; John J. Mayer; Sophie C. McKee (Mammal Research, 2024)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Food Web Fuel Differs Across Habitats and Seasons of a Tidal Freshwater Estuary - Matthew Young; Emily Howe; Teejay O’Rear; Kathleen Berridge; Peter Moyle (Estuaries and Coasts, 2021)
Estuarine food webs are fueled by multiple different primary producers. However, identifying the relative importance of each producer to consumers is difficult, particularly for fishes that utilize multiple food sources due to both their mobility and their generally high trophic levels. Previous studies have documented broad spatial differences in the importance of primary producers to fishes within the Upper San Francisco Estuary, California, including separation between pelagic and littoral food webs. In this study, we evaluated the importance of primary producers to adult fishes in three closely spaced subregions that represented disparate habitat types (a tidal wetland channel, a turbid backwater channel, and a deep open-water channel), each a potential outcome of local restoration projects. Using stable isotope analysis coupled with a Bayesian mixing model, we identified significant differences in primary-producer contribution to fishes and invertebrates across habitats and seasons, especially in the relative contribution of submersed aquatic vegetation and phytoplankton. Most fishes utilized multiple primary producers and showed little segregation between pelagic and littoral food webs among habitats. Availability of primary producers differs seasonally and across multiple spatial scales, helping to buffer environmental variability and thus enhancing food web resilience. Ecosystem restoration may improve with emphasis on restoring a wide variety of primary producers to support consumers.

Using Stable Isotopes to Assess the Contribution of Terrestrial and Riverine Organic Matter to Diets of Nearshore Marine Consumers in a Glacially Influenced Estuary - Emily J. Whitney; Anne H. Beaudreau; Emily R. Howe (Estuaries and Coasts, 2018)

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

Restored connectivity facilitates recruitment by an endemic large‐seeded tree in a fragmented tropical landscape - Marinés de la Peña‐Domene; Emily S. Minor; Henry F. Howe (Ecology, 2016)
Many large‐seeded Neotropical trees depend on a limited guild of animals for seed dispersal. Fragmented landscapes reduce animal abundance and movement, limiting seed dispersal between distant forest remnants. In 2006, experimental plantings were established in pasture to determine whether plantings enhance seed dispersal and, ultimately, seedling recruitment. We examined patterns of naturally recruited seedlings of Ocotea uxpanapana, a large‐seeded bird‐dispersed tree endemic to southern Mexico that occurs in the surrounding landscape. We used GIS and least‐cost path analysis to ask: (1) Do restoration efforts alter recruitment patterns? (2) What is the importance of canopy cover and likely dispersal pathways to establishment? Patterns of seedling establishment indicated that dispersal agents crossed open pastures to wooded plots. Recruitment was greatest under woody canopies. Also, by reducing movement cost or risk for seed dispersers, wooded canopies increased influx of large, animal‐dispersed seeds, thereby restoring a degree of functional connectivity to the landscape. Together, canopy openness and path distance from potential parent trees in the surrounding landscape explained 73% of the variance in O. uxpanapana seedling distribution. Preliminary results suggest that strategic fenced plantings in pastures increase dispersal and establishment of large‐seeded trees, thereby accelerating forest succession in restorations and contributing to greater connectivity among forest fragments.

Using Isotopic Measures of Connectivity and Ecosystem Capacity to Compare Restoring and Natural Marshes in the Skokomish River Estuary, WA, USA - Emily Howe; Charles A. Simenstad (Estuaries and Coasts, 2015)

Isotopic Determination of Food Web Origins in Restoring and Ancient Estuarine Wetlands of the San Francisco Bay and Delta - Emily R. Howe; Charles A. Simenstad (Estuaries and Coasts, 2011)